DIVERSIFIKASI PRODUKSI: STUDI EKONOMI POLITIK PEDESAAN DI JAWA - Utama, Aji Prasetya Wahyu (Forum Ilmu Sosial, 2014)
This paper contains the diversification of production that influences the social differentiation processes in rural community. Every society have different life strategies that is different from another, including village forestry society. Besides directly use the forest product, they also work in agriculture, palm sugar economic, coffee plantation, and animal husbandry. Interestingly, each of these economic resources have different role in the household economic. It's also affects to make economic class formation in rural society. I use the mode of production analysis to make it ease to understand the individual ownership that determine the level of rural economic class.